A STRUCTURE BASED MOLECULAR DOCKING OF Acacia catechu AGAINSTCONTRACTILE PROTEIN Plasmodium falciparum – A MALARIAL DISEASE (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The bioactive compounds of Acacia catechu using Gas Chromatography Mass Spectroscopy and the inhibitory activity against contractile protein Plasmodium falciparum against protozoan disease were studied. This research mainly focuses on finding of novel drug screening against malarial enzyme. The compounds of Acacia catechu are screened using Lipinski rule of five with ADMET properties in which the character as well as behaviour of the drug compound is known. The compounds were checked for its dosage level in human and rat as well as distribution properties in blood brain barrier and central neuro system. The compounds 9,12,15- Octadecatrienoic acid has higher affinity with -7.95 Kcal/mol followed by Pthalic acid, butyl 2- pentyl ester -7.35 Kcal/mol and Furo[2,3-d] Pyrimidine-4,6 [5H,7H]-dion -6.24 Kcal/mol were docked using Autodock software. the compound 9,12,15- Octadecatrienoic acid, Pthalic acid butyl 2- pentyl ester, Furo[2,3-d] Pyrimidine-4,6 [5H,7H]-dion has higher affinity such as -7.95 Kcal/mol , -7.35 Kcal/mol and -6.24 Kcal/mol respectively. Thus this research proves that the drug compounds of Acacia catechu have novel therapeutic drug activity against virulent enzymes.